Serotype distribution and antimicrobial resistance of Streptococcus pneumoniae causing noninvasive diseases in a Children's Hospital, Shanghai - Pan,Fen (2015)
Background: Streptococcus pneumoni ae, which cause noninvasive pneumococcal diseases, severely impair children's health. This study analyzed serotype distribution and antimicrobial resistance of S. pneumoni ae from January 2012 to December 2012 in a Children's Hospital, Shanghai. Methods: A total of 328 pneumococcal isolates were serotyped by multiplex sequential PCR and/or capsule-quellung reaction. The minimum inhibitory concentrations for 11 antimi- crobial agents were determined by broth microdilution method. Results: Among 328 strains, 19F (36.3%), 19A (13.4%), 6A (11.9%), 23F (11.0%), 14 (5.8%), 6B (5.2%), and 15B/C (4.3%) were the most common serotypes. The coverage rates of 7-, 10-, and 13-valent conjugate vaccines (PCV7, PCV10, and PCV13) were 58.2%, 58.2%, and 84.1%, respectively. Out of the isolates, 26 (7.9%) strains were penicillin resistant. Most of the strains displayed high resistance rate to macrolides (98.5% to erythromycin, 97.9% to azithromycin, and 97.0% to clindamycin). Conclusions: The potential coverage of PCV13 is higher than PCV7 and PCV10 because of the emergence of 19A and there should be long-term and systematic surveillance for non-vaccine serotypes.